Dementia and diet for dementia prevention in older persons - Chaiyasung, Phatcharaphan; Thepsatitporn, Sarawin; Machompoo, Niyom; Sirisome, Jirawun (Thai Journal of Nursing, 2021)
Thailand is an ageing society which has great impacts on Thai socity, especially on health problem. Dementia is a common problem in older person that causes them to become a dependent. This affects on the quality of life of older persons, caregivers, and their families. Factors related to dementia can be divided into 3 groups including demographic and social factors, health condition, and behavior. Food is the one essential factor associated with dementia. To support efficient brain functions, human body needs nutrients. Lack of nutrients and malnourishment are the risk of dementia. Foods are beneficial that can protect against dementia.